The study of learning styles in middle school monolingual and bilingual students and its relationship with educational achievement and gender (فصلنامه نوآوری‌های آموزشی, 2007)
The purpose of doing the research which is the basis for writing this article, was the study and comparison of learning styles in bilingual students (Turkish and Kurdish) and those students who speak one language only (Farsi), and research into whether there exists a relationship between methods of learning and educational advancement elements and the gender among these students. Due to this fact, Felder-Solomon Learning-style questionnaire was put to work for 720 students in grade 6, 7, and 8 of public schools in 2001-2002 academic year. The students were consisted of 240 bilingual Kurdish female and male students, 240 bilingual Turkish female and male students, and 240 one-language speaking (Farsi) female and male students, respectively in cities of Sanandaj, Tabriz, and Tehran. The outcomes were analyzed with the help of multivariate analysis of variance and the correlational method. This research showed that: a) There is difference between the learning style of bilingual (Turk and Kurd speaking) students andstudents who speak only one language (Farsi), in the way that the one-language speaking students have an intuitional-visual learning style in comparison with the bilingual students. The bilingual students have a sensational-verbal learning style compared to the onelanguage speaking students. b) There is no significant relationship between the learning style and the student’s educational advancement. c) There is a difference between the learning methods of female and male students; in the way that boys’ learning style is of the visual-holistic type, while the girls’ learning style is of the verbal-consecutive type.